2022
DOI: 10.3389/fonc.2022.861928
|View full text |Cite
|
Sign up to set email alerts
|

PI-RADS v2.1 Combined With Prostate-Specific Antigen Density for Detection of Prostate Cancer in Peripheral Zone

Abstract: PurposeTo evaluate the diagnostic performance of combining the Prostate Imaging Reporting and Data System (PI-RADS) scoring system v2.1 with prostate-specific antigen density (PSAD) to detect prostate cancer (PCa).MethodsA total of 266 participants with suspicion of PCa underwent multiparametric magnetic resonance imaging (mpMRI) in our hospital, after at least 4 weeks all patients underwent subsequent systematic transrectal ultrasound (TRUS)-guided biopsy or MRI-TRUS fusion targeted biopsy. All mpMRI images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Compared with conventional methods that depend on digital rectal examination (DRE) or transrectal ultrasonography (TRUS)–guided biopsy alone, mpMRI demonstrated higher accuracy and thus could substantially reduce unnecessary biopsies ( 6 8 ). In recent years, various novel models and nomograms were developed to improve the diagnostic performance of PCa, which utilizes one or more of following tools or biomarkers: serum prostate-specific antigen density (PSA), PSAD, age, history of prior prostate biopsy, DRE, radiomics, genomics, and molecular imaging ( 9 , 10 )…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional methods that depend on digital rectal examination (DRE) or transrectal ultrasonography (TRUS)–guided biopsy alone, mpMRI demonstrated higher accuracy and thus could substantially reduce unnecessary biopsies ( 6 8 ). In recent years, various novel models and nomograms were developed to improve the diagnostic performance of PCa, which utilizes one or more of following tools or biomarkers: serum prostate-specific antigen density (PSA), PSAD, age, history of prior prostate biopsy, DRE, radiomics, genomics, and molecular imaging ( 9 , 10 )…”
Section: Introductionmentioning
confidence: 99%
“…According to recent literatures, PSAd is an important predictive indicator for csPCa compared to traditional tPSA, and has a broader prospect. The strategy of mpMRI combined with PSAd can effectively detect PI-RADS 1–3 cases and tumors in peripheral zone lesions with extremely high negative predictive values ( 15 - 17 ). Therefore, we subsequently compared two schemes of the prediction model, PI-RADS + SUVmax + PSAd and PI-RADS + SUVmax.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the complementary effect of PSAd and mpMRI, Wei et al incorporated PSAd into the predictive model based on mpMRI, which significantly improved the performance in diagnosing csPCa in the transitional zone ( 27 ). Similarly, Wen et al constructed a clinical predictive model based on PSAd and mpMRI, and the results showed that it could significantly improve the diagnostic performance of tumors in peripheral zone ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the PSAD and f/tPSA have good differential diagnostic efficacy and sensitivity for csPCa and non-csPCa, their specificity is relatively low. Wen et al [ 25 ] showed that PSAD is an independent predictor of PCa (PZ: OR = 37.66, 95% CI = 3.3–429.1, p = 0.002; TZ: OR = 14.57, 95% CI = 4.64–45.76, p < 0.001). However, PSA and PGV were not investigated thoroughly because they are strongly correlated with PSAD.…”
Section: Discussionmentioning
confidence: 99%